HUBUNGAN ANTARA KEMAMPUAN MANAJERIAL DAN PENGAWASAN DENGAN PRODUKTIVITAS KEPALA KOMPETENSI KEAHLIAN DI SMK NEGERI DKI JAKARTA - Suharto Suharto (Jurnal Manajemen Pendidikan, 2012)
This Research is made to determine (1) the relationship between managerial skills with Head of Competence Skills productivity (2) the relationship of control activity to the Head of Competence Skills productivity (3) the relationship between managerial and control skills along with the Head of Competence Skills productivity. The research methodology that has been used was correlation approach survey. In this study, 145 Head of Skill Competency in selected SMK have been used as a sample by using simple random sampling techniques (simple random sampling). This research conducted in Jakarta area. Based on the description to hypothesis test, the research findings can be outlined as followed: (1) there is a positive relationship between managerial skills with the productivityof the Head of Competence Skills (2) there is a control relationship with the productivity of Head Competency Skills (3) there is a positive relationship between managerial ability andcontrol alongwith the Head of Competence Skills productivity. The implication of this study is an attempt of improving the productivity of the Head of Skill Competency that can be done through improved managerial and controlskills.